Salmonella spp.: relevância do patógeno diante da expansão comercial da carne ovina - Pereira, Juliano Gonçalves [UNESP]; Soares, Vanessa Mendonça [UNESP]; Izidoro, Thiago Braga [UNESP]; Pinto, José Paes de Almeida Nogueira [UNESP] (My University, 2010)
In recent years, the slaughter and consumption of sheep meat and meat products have increased significantly and as the demand for products from sheep increases the risks associated with consumption of these products rise in the same proportion. The organism involved in most foodborne diseases is Salmonella, a bacterium that has a reservoir the intestinal tract of humans and animals. Few data are found in the literature on the prevalence of Salmonella in sheep, unlike other countries where concern for the consumption of sheep infected by this pathogen leads to scientific research, which they seek to evaluate the risks of eating food contaminated with Salmonella. In view of these facts, the objective was to collect data through the literature on the occurrence of Salmonella in sheep, supporting and promoting research on this subject.

Nos últimos anos, o abate de ovinos e o consumo de carne e derivados vêm aumentando significativamente e à medida que a demanda por produtos de origem ovina aumentam, os riscos associados ao consumo de tais produtos crescem na mesma proporção. O microrganismo mais envolvido em surtos por ingestão de alimentos contaminados é Salmonella, bactéria que tem como reservatório o trato intestinal de humanos e animais. Poucos dados são encontrados na literatura nacional sobre a prevalência de Salmonella em ovinos, ao contrário de outros países, onde a preocupação com o consumo de produtos ovinos contaminados por esse patógeno incentiva pesquisas científicas na qual se buscam avaliar os riscos da ingestão de alimentos contaminados com Salmonella. Tendo em vista estes expostos, o objetivo deste trabalho foi levantar dados através da pesquisa bibliográfica sobre a ocorrência de Salmonella em ovinos, embasando e fomentando pesquisas a respeito deste assunto.
Salmonella spp.: relevance of the pathogen on the commercial expansion of the sheep meat
Keywords: Contamination; Salmonella; Sheep meat; Carne ovina; Contaminação; Salmonella